# 2x+2(7x+300)=50000

## Simple and best practice solution for 2x+2(7x+300)=50000 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2x+2(7x+300)=50000 equation:

Simplifying 2x + 2(7x + 300) = 50000 Reorder the terms: 2x + 2(300 + 7x) = 50000 2x + (300 * 2 + 7x * 2) = 50000 2x + (600 + 14x) = 50000 Reorder the terms: 600 + 2x + 14x = 50000 Combine like terms: 2x + 14x = 16x 600 + 16x = 50000 Solving 600 + 16x = 50000 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-600' to each side of the equation. 600 + -600 + 16x = 50000 + -600 Combine like terms: 600 + -600 = 0 0 + 16x = 50000 + -600 16x = 50000 + -600 Combine like terms: 50000 + -600 = 49400 16x = 49400 Divide each side by '16'. x = 3087.5 Simplifying x = 3087.5

### See similar equations:

| 7x+300=50000 | | y^3-1= | | y^2-y+1= | | h=195t-16t^2 | | 2x+10=85 | | 5(c+7)=80 | | 4x-15=85 | | 28-(x+6)=5x-2 | | 2x+8x-5=1 | | 6y+9=5y-7 | | 23y-6y+y-8=1 | | 5x+2=2x+50 | | 18=4+38t-16t^2 | | 2x^2-2x= | | 65=65-10t-16t^2 | | w^2-2w-63= | | g-5/3=5/3 | | 26=54t+-5t^2 | | -2.9+(-5.2)= | | 6x-18=11x-28 | | 12(3x+4)-7(2x-3)=2x-31 | | 9c-(2m+1)=20 | | 0.15x+.05(16-x)=.10(16) | | y^2-3y+9= | | 9(x)/13=13 | | 9(x)/13=36 | | 16=30t-16t^2 | | 0.6(x+10)+0.6x=42 | | 36=9h | | 1.8(k-273.15)+32=f | | 16=3+30t-16t^2 | | 2(9S+10)-35=3(5S+6)-23 | | (3-6q)=-18 | | 95=5(2n+6)+5 | | 16=-8n-8n | | 16x=12x-2x^2 | | k=10 | | 7+5x+5=-13 | | -8v-4=-4-6v | | 8t=3(t+55) | | 50=50-10t-5t^2 | | -8k+2k=12 | | a=b+XP | | 50=10t-5t^2 | | -4n-2n=24 | | -6x+x=5 | | 3(y*4)=24 | | 6x-7=6x-3 | | -6r+8r=-12 | | 26y-4-11y=15y+6 | | -5p+4-5=19 | | 3-6x+7x=-1 | | 10=2x+1-1 | | f(5a)+3=f(3a)+117 | | 2-4h=h-3 | | -1+7m-1=12 | | 16+10x=14x-4 | | -1t=8 | | 90x=100+70x | | 2x-4=2+8x | | 3=7x+4-8 | | f(5a)+3=f(3a)+11 | | 6(1+6n)+2=-136 | | -118=-6+8(n-7) | | x+4x-30=180 |